2016
DOI: 10.1039/c5cp05831g
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic, magnetic and chemical properties of B-, C- and N-doped MgO(001) surfaces

Abstract: Doping of simple oxide materials can give rise to new exciting physical and chemical properties and open new perspectives for a variety of possible applications. Here we use density functional theory calculations to investigate the B-, C- and N-doped MgO(001) surfaces. We have found that the investigated dopants induce magnetization of the system amounting to 3, 2 and 1 μB for B, C and N, respectively. The dopants are found to be in the X(2-) state and tend to segregate to the surface. These impurity sites als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 54 publications
8
21
0
Order By: Relevance
“…For all the considered dopants and the nanotube sizes (from (MgO) 6 to (MgO) 15 ) we found that dopants preferred the edge sites of the nanotube. This is in agreement with the results reported for the C-doped multiwall MgO nanotubes [20], and the MgO(001) terraces doped with B, C and N [21].…”
Section: Structural Electronic and Magnetic Properties Of Doped Mgosupporting
confidence: 93%
See 4 more Smart Citations
“…For all the considered dopants and the nanotube sizes (from (MgO) 6 to (MgO) 15 ) we found that dopants preferred the edge sites of the nanotube. This is in agreement with the results reported for the C-doped multiwall MgO nanotubes [20], and the MgO(001) terraces doped with B, C and N [21].…”
Section: Structural Electronic and Magnetic Properties Of Doped Mgosupporting
confidence: 93%
“…It is the most apparent for B, and the effect decreases towards N, as discussed in Ref. [21]. For F and Li, having 2s 2 np 5 [19].…”
Section: Structural Electronic and Magnetic Properties Of Doped Mgomentioning
confidence: 72%
See 3 more Smart Citations